Clustering of Consumer Perceptions toward Processed Chicken Meat Products to Support Regional Food Security - Ratna Ekawati; Nuraida Wahyuni; Rezka Hapsari Mega Nadia (Universitas Darussalam Gontor, 2025)
This study aims to classify micro, small, and medium enterprises (MSMEs) in the agroindustry sector based on their performance and sustainability characteristics using the K-Means clustering method. The analysis was conducted to identify homogeneous groupsof MSMEs that share similar attributes in innovation, efficiency, value addition, and sustainable practices. The optimal number of clusters was determined using the Dunn Index, which evaluates the compactness and separation of clusters. The results indicate that the highest Dunn Index value was obtained for three clusters (0.24), compared to two clusters (0.23), four clusters (0.22), and five clusters (0.17).This finding suggests that a three-cluster model provides the most optimal structure, balancing within-cluster cohesion and between-cluster separation. The visualization of the clustering results further demonstrates distinct groupings among MSMEs, corresponding to high-performing, moderate, and developing enterprises. These results provide valuable insights for policymakers and stakeholders in designing targeted strategies to enhance competitiveness and sustainability in the agroindustry sector.